Combined 20-gauge and 23-gauge pars plana vitrectomy for the management of posteriorly dislocated lens: a case series - Kongsap, Pipat (Dove Medical Press, 2010)
OBJECTIVE: To present a new surgical approach for the management of posteriorly dislocated lens by using a combination of 20-gauge (20G) and 23-gauge (23G) pars plana vitrectomy. DESIGN: An interventional case series METHODS: This technique was performed on six patients (five men, one woman; mean age, 66.67 years; range, 66–72 years). Two 23G trans-conjunctival sclerotomy ports were created for infusion and illumination along with a 20G sclerotomy port for introducing the vitrectomy probe or fragmatome. RESULTS: This procedure was successfully performed on six eyes. On postoperative day one, the media were clear and the retina could be seen by indirect ophthalmoscopy. Hyphema developed in one eye and resolved within a week. There were no observed cases of retinal tear, wound leakage, hypotony, or endophthalmitis. The post-operative follow-up period ranged from three to twelve months (mean, 8.1 months). By the final visit, two patients had achieved a visual acuity of 20/40 or better, three patients, 20/70, and one patient, 20/200. CONCLUSION: The combination of 20G and 23G pars plana vitrectomy is an efficacious and safe procedure for management of posteriorly dislocated lens.